Time and History. Proceedings of the 28. International Ludwig Wittgenstein Symposium, Kirchberg am Wechsel, Austria 2005 - Stadler, Friedrich (Publications of the Austrian Ludwig Wittgenstein Society - New Series (N.S.), 2006)
This wide-ranging collection of essays contains eighteen original articles by authors representing some of the most important recent work on Wittgenstein. It deals with questions pertaining to both the interpretation and application of Wittgenstein's thought and the editing of his works. Regarding the latter, it also addresses issues concerning scholarly electronic publishing. The collection is accompanied by a comprehensive introduction which lays out the content and arguments of each contribution.